PENGARUH SUGESTI TERHADAP PERKEMBANGAN PSIKOLOGI ANAK - Trinurmi, Sitti (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
Suggestions are part of hypnosis. Hypnosis among the public is still a scary thing and part of black magic. The subconscious mind is more neutral and suggestive. The subconscious mind can be assumed to be a long-term human memory that stores various circumstances, events based on the experience of self or others. The influence of suggestion greatly affects the development of children because suggestions are stimuli, influences, or stimuli that an individual gives to other individuals in such a way that the person who is advised obeys or performs what he or she suggests without thinking again critically and rationally. Especially for children who are still unstable so the selection of the right word or language is very helpful for parents in giving suggestions to children. Suggestions can be done in the child's environment where they grow and develop, namely the family environment, school environment and community environment. A suggestion will be stored in the subconscious mind, which will affect the child's behavior, character, and mindset. Parents can reprogram a child's subconscious mind by giving positive suggestions through the use of positive language and not using negative language, as well as providing affectionate behavior. Sensitivity is the main key in building approaches and planting suggestions to children.